(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
ABSTRACT This study investigates the phytochemical composition and aldose reductase (AR) inhibitory potential of ethanolic seed extracts from Trigonella foenum graecum (fenugreek). Qualitative and quantitative analyses confirmed the presence of alkaloids, flavonoids, saponins, tannins, and polyphenols, with saponins (87.56% total content) and flavonoids (68.25%) as dominant constituents. GC-MS analysis identified major bioactive compounds, including methyl α-D-glucopyranoside (74.54% peak area) and 3-O-methyl-D-glucose (16.11%). Aldose reductase inhibitory activity was assessed in vitro, and ethanol extract showed the highest potency. (IC50 = 101.35 ± 12.75 μg/mL), surpassing ethyl acetate and n-hexane extracts. Fractionation via column chromatography yielded six fractions (A–F), with Fraction B showing potent AR inhibition (IC50 = 84.58 ± 19.61 μg/mL), comparable to quercetin (71.23 ± 21.47 μg/mL). FTIR of Fraction B revealed functional groups (O–H, C=O, N–O) associated with bioactive compounds. These results highlight fenugreek’s potential as a natural source for managing diabetic complications via AR inhibition. These findings support the ethnomedicinal use of T. foenum-graecum and warrant further studies for therapeutic development